Pola Komunikasi keluarga Dengan Work Life Pada Karyawan Bank Syariah Indonesia - Angel Anandita; Eraskaita Ginting; Sonia Nurprameswari (Universitas Muhammadiyah Klaten, 2025)
Work life balance is the ability to balance work with personal life to achieve a good quality of life. Imbalances can trigger stress, family conflicts, and mental health disorders. Factors such as time management, stress management, workload, and social demands contribute to this balance. The purpose of this study is to find out how the pattern of family communication with work-life balance in employees of Bank Syariah Indonesia Sudirman Palembang Branch Office. This study uses a qualitative method with a phenomenological approach. This study uses the role theory developed by Ralph Linton in 1936, the informants in this study are 10 informants. The results of the study showed that the informants tried to maintain a balance by prioritizing family at important times. Family communication patterns in managing work-life balance are reflected through proactive communication, the use of technology, and quality time together. Informants maintain emotional connections by involving families in time-related decision-making, informing families if work requires extra time, and spending time together outside of work hours. This strategy is in line with role theory, which emphasizes the importance of effective communication and time management to reduce conflict, maintain balance, and support the psychological and social well-being of employees. The results of this study have important implications for employees, companies, and families in supporting work-life balance. Companies, especially Bank Syariah Indonesia Sudirman Palembang Branch Office, can consider policies that support work flexibility, workload management, and employee welfare programs to reduce stress and increase productivity.